Analytical and Stochastic Modeling Techniques and Applications 17th International Conference, ASMTA 2010, Cardiff, UK, June 14-16, 2010. Proceedings - Al-Begain, Khalid; Fiems, Dieter; Knottenbelt, William J.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the 17th International Conference on Analytical and Stochastic Modeling Techniques and Applications, ASMTA 2010, held in Cardiff, UK, in June 2010. The 28 revised full papers presented were carefully reviewed and selected from numerous submissions for inclusion in the book. The papers are organized in topical sections on queueing theory, specification languages and tools, telecommunication systems, estimation, prediction, and stochastic modelling.
Queueing Theory I -- A Batch-Service Queueing Model with a Discrete Batch Markovian Arrival Process -- Queueing System MAP/PH/N with Propagated Failures -- Analysis of a Discrete-Time Queueing System with an NT-Policy -- Packet Loss Minimization in Load-Balancing Switch -- Queueing Theory II -- The Preemptive Repeat Hybrid Server Interruption Model -- Networks of Symmetric Multi-class Queues with Signals Changing Classes -- Product-Form Solutions for Models with Joint-State Dependent Transition Rates -- The qnetworks Toolbox: A Software Package for Queueing Networks Analysis -- Specification Languages and Tools -- Rewriting Logic Based Performance Estimation of Embedded Systems -- A Formal Language toward the Unification of Model Checking and Performance Evaluation -- Security Evaluation of Layered Intrusion Tolerant Systems -- Stochastic PERT and CAST Logic Approach for Computer Support of Complex Operation Planning -- Telecommunication Systems I -- Perfect Sampling of Load Sharing Policies in Large Scale Distributed Systems -- Stochastic Comparisons for Performability of Telecommunication Systems -- Model-Based Stochastic Simulation of P2P VoIP Using Graph Transformation System -- Performance Evaluation of Media Segmentation Heuristics Using Non-markovian Multi-class Arrival Processes -- Telecommmunication Systems II -- A Formal Approach to Investigate the Performance of Modern E-commerce Services -- Leader Election in Anonymous Radio Networks: Model Checking Energy Consumption -- Upper Bound on Overall Delay in Wireless Broadband Networks with Non Real-Time Traffic -- Estimation -- Robustness of the Whittle Estimator Applied to Non-Gaussian Long-Range Dependent Processes -- Service Time Estimation with a Refinement Enhanced Hybrid Clustering Algorithm -- Invariant Embedding Technique and Its Applications for Improvement or Optimization of Statistical Decisions -- Prediction -- Prediction Model Selection and Spare Parts Ordering Policy for Efficient Support of Maintenance and Repair of Equipment -- Prediction-Based Dynamic Target Interception Using Discrete Markov Chains -- Neural Networks as Surrogate Models for Measurements in Optimization Algorithms -- Stochastic Modelling -- Limit Behavior of the Hybrid Approximation of Stochastic Process Algebras -- Analysis of an Automated Auction with Concurrent Multiple Unit Acceptance Capacity -- Congestive Collapse and Its Avoidance in a Dynamic Dial-a-Ride System with Time Windows.
Keywords: Computer science; Computer Communication Networks; Computer system performance; Software engineering; Computer software; Information systems; Computer Science; Software Engineering; Computer Communication Networks; System Performance and Evaluation; Information Systems Applications (incl.Internet).; Probability and Statistics in Computer Science; Algorithm Analysis and Problem Complexity